Hydrogen bond serving as a protecting group to enable the photocatalytic [2+2] cycloaddition of redox-active aliphatic-amine-containing indole derivatives. Issue 19 (16th February 2022) - Li, Hao; He, Yishu; Zhang, Di; Yang, Li; Zhang, Jiarui; Long, Rui-ling; Lu, Ji; Wei, Jun; Yang, Lin; Wei, Siping; Yi, Dong; Zhang, Zhijie; et al.
Abstract : We describe a photocatalytic [2+2] cycloaddition of redox-sensitive aliphatic-amine-containing indole derivatives assisted by a hydrogen bond, which affords a range of cyclobutane-fused polycyclic indoline derivatives, especially bridged-cyclic indolines. Abstract : Redox-sensitive functionalities such as aliphatic amines with low oxidation potentials and easily oxidized by photocatalysts are generally not compatible with photocatalytic reactions. We describe a hydrogen-bond-assisted visible-light-mediated [2+2] cycloaddition of redox-sensitive aliphatic-amine-containing indole derivatives providing a range of cyclobutane-fused polycyclic indoline derivatives, especially bridged-cyclic indolines. Mechanistic studies indicated that the success of the reaction was based on on the formation of H-bonds between the N-atom and alcohol proton of TFE or HFIP, with this formation preventing or blocking the single-electron transfer from the aliphatic amine functionality to the excited photocatalyst.